Efficacy and safety of HBM4003 combined with toripalimab in refractory neuroendocrine neoplasms: a multicenter, phase II studyResearch in context - Panpan Zhang; Kai Chen; Jianwei Yang; Lijie Song; Fei Zheng; Ruixuan Luo; Yebo He; Feng Li; Di Yang; Nan Cao; Xiaolu Tao; Lin Shen; et al. (EClinicalMedicine)
Summary: Background: High-grade neuroendocrine neoplasms (NENs) have limited treatment options following first-line platinum-based chemotherapy, often resulting in poor clinical outcomes. Dual immune checkpoint blockade targeting CTLA-4 and PD-1 offers a synergistic approach by enhancing T-cell activation and amplifying anti-tumor immune responses. This study evaluates the efficacy and safety of HBM4003, a novel fully human anti-CTLA-4 monoclonal antibody, in combination with toripalimab, a PD-1 inhibitor, in patients with high-grade, refractory NENs. Methods: This multicenter, open-label, phase II study enrolled patients with neuroendocrine carcinomas (NECs), grade 3 NETs (NETs G3), and mixed neuroendocrine-non-neuroendocrine neoplasms (MiNENs) who had progressed on first-line therapy. Patients received HBM4003 at either 0.3 mg/kg or 0.45 mg/kg in combination with toripalimab (240 mg) every three weeks. The primary endpoint was the objective response rate (ORR). The study was registered on ClinicalTrials.gov (NCT05167071). Findings: Between December 2021 and May 2024, a total of 29 patients were enrolled (NECs, n = 22; NETs G3, n = 3; MiNENs, n = 4). All patients had previously undergone chemotherapy, with 11 receiving ≥2 lines of therapy. Thirteen (13) patients had lung metastasis and 18 had liver metastasis. Patients were assigned to the HBM4003 0.3 mg/kg cohort (n = 13) or the 0.45 mg/kg cohort (n = 16), with 26 patients forming the efficacy analysis set. The overall ORR was 34.6% (95% confidence intervals [CI], 17.2–55.7), and the disease control rate (DCR) was 65.4% (95% CI, 44.3–82.8). Median progression-free survival (PFS) and overall survival (OS) were 4.0 months (95% CI, 1.6–5.1) and 21.8 months (95% CI, 16.7-not estimated [NE]), respectively. For 19 NEC patients in the efficacy analysis set, the ORR and DCR were 36.8% (95% CI, 16.3–61.6) and 68.4% (95% CI, 43.4–87.4), respectively. The median PFS was 4.0 months (95% CI, 1.6–5.4), while the median OS was not reached (95% CI, 13.5-NE). Of the 29 NEN patients receiving at least one dose of study treatment, all patients experienced at least one treatment-related adverse event (TRAE), with 10 (34.5%) experiencing grade ≥3 TRAE and eight (27.6%) experiencing grade ≥3 immune-related adverse events. Interpretation: HBM4003 combined with toripalimab demonstrated promising anti-tumor activity and manageable safety in patients with refractory NENs, supporting further investigation of this combination therapy. Funding: This study was funded by Harbour BioMed (Shanghai) Co. Ltd.